Fiscal policy effectiveness: Lessons from the Great Recession - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2011)
This paper reconsiders fiscal policy effectiveness in light of the recent economic crisis. It examines the fiscal policy approach advocated by the economics profession today and the specific policy actions undertaken by the Bush and Obama administrations. An examination of the labor market renders the contemporary aggregate demand-management approach wholly inadequate for achieving certain macroeconomic objectives, such as the stabilization of investment and investor expectations, the generation and maintenance of full employment, and the equitable distribution of incomes. The paper reconsiders the policy effectiveness of alternative fiscal policy approaches, and argues that a policy that directly targets the labor demand gap (as opposed to the output gap) is far more effective in stabilizing employment, incomes, investment, and balance sheets.
Keywords: E24; E25; E65; J08; J6; 330; The Great Recession; fiscal policy; macroeconomic stabilization; employment